Planning with multiple criteria : investigation, communication, and choice - Bogetoft, Peter (Copenhagen Business School Press, 1997)
Annotation This book introduces basic notions of how and why we plan, both as individuals and within the context of an organization.
Keywords: Multiple criteria decision making.; elektronické knihy; electronic books